PENGARUH MEDIA PEMBELAJARAN BERBASIS GAMIFIKASI TERHADAP HASIL BELAJAR BAHASA INDONESIA KELAS V SDN 117505 PANJANG TONGAH - Ummi Nadhrah; Natalia Silalahi; Khairul Usman (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to determine the effect of gamification-based learning media through the Padlet application on Indonesian language learning outcomes in the material "Self-Expression through Hobbies" for fifth-grade students at SDN 117505 Panjang Tongah in the 2025/2026 academic year. The type of research used is quantitative research with a quasi-experimental method and a nonequivalent control group design. The study population was all fifth-grade students, totaling 50 students. The sample was determined using a purposive sampling technique, with class V-A as the experimental class that received treatment using gamification-based learning media (Padlet), totaling 23 students, and class V-B as the control class with conventional learning, totaling 27 students. The research instrument used a multiple-choice test consisting of 20 questions that had been tested for validity, reliability, difficulty level, and discriminating power. Data analysis techniques used normality tests, homogeneity tests, and hypothesis testing with an independent sample t-test. The results showed a significant difference in learning outcomes between the experimental class and the control class. The average posttest score of the experimental class was 88.04, higher than the control class's 63.33. The hypothesis test results obtained a significance value of 0.000 < 0.05 and a t-count of 8.298 > t-table 2.010, so H1 was accepted and H0 was rejected. Thus, it can be concluded that there is a significant effect of using gamification-based learning media through the Padlet application on the Indonesian language learning outcomes of fifth-grade students at SDN 117505 Panjang Tongah